Jewish Representation in British Literature 1780-1840 - Scrivener, M. author. aut Link
VII, 270 p.
Keywords: Describing Jewish representation by Jews and Gentiles in the British Romantic era from the Old Bailey courtroom and popular songs to novels, poetry, and political pamphlets, Scrivener integrates popular culture with belletristic writing to explore the wildly varying treatments of stereotypical Jewish figures.